Women's squash team (Tufts Archival Research Center, 2015)
photographic print. Back Row (Left to Right): Penny Wilson, Carolina Ramon, Stacia Sandberg, Ann Marie Rosas, Head Coach Bill Summers. Front Row (Left to Right): Robin Natiss, Louisa Terrell, Captain Marie Kwek, Kim Rance, Erica Kerner, Melissa MacGillivray.